The Impact of Learning Together Method Based Lesson Study on Students’ Self-Awareness in Speaking Class - Elis Susanti (STKIP PGRI Lubuklinggau, 2018)
Language learning is affected by many factors including cognitive and affective factors. One of the affective factors which plays significant role to stimulate students’ motivation which then finally lead to help them achive the targeted achievement is self-awareness. Self-awareness is an affective facet of an individual which makes them able to understand their self-emotion and others, so it creates a good self-control within oneself. Self-awareness also helps an indivisual to recognize their strengths and weaknesses which encourage a good self-confident. This research was to investigate how the implementation of learning together method based lesson study affects students’ self-awareness. This research applied mixed-method (quantitative and qualitative method) in which the quantitative data was obtained from a questionnaire administered to the research sample after three learning cycles of lesson study applied. Meanwhile, the qualitative data was obtained throughout an observation during the teaching and learning process. The research sample was the third semester of English Education Study Program in STKIP Muhammadiyah kotabumi. Based on the research result, it is found that students’ self-awareness are high during the teaching and learning process throughout learning together method based lesson study so students enjoyed the teaching and learning process and they are easy to understand the material given.